Advances in Turbomachinery - Cemal Kushan, Melih; Yazar, Isil (IntechOpen, 2023)
Turbomachinery refers to machines such as turbines, compressors, and pumps that transfer energy between a rotor and a fluid. This book provides a comprehensive overview of turbomachinery with two sections: "Turbomachinery Problems" and "Turbomachinery Solutions". Problems discussed include erosion, distortion, and instability. Solutions explored include diagnosis methods like rhythmograms and scatterograms.